The chemical synthesis, pharmaceutical preparation and toxicity analysis of fluorodopa for positron emission tomography (PET) brain imaging in South Africa - Cromarty, Allan Duncan (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2010.